The study on the Energy Consumption of middle school facilities in Daegu, Korea - TaeWoo Kim; ByungJoo Kang; Hyuntae Kim; ChoonWook Park; Won-Hwa Hong (Energy Reports, 2019)
Recently, Korea has upgraded the luminance standard of classrooms and started to introduce the air-conditioning system in order to enhance pleasantness of the learning environment. In addition, as use of auxiliary equipment, such as TV, VTR and computer, is increasing and due to school meals, energy consumption is increasing in school facilities. Despite the increase of energy consumption of school facilities, however, it is difficult to find actual data on energy consumption. Therefore, in this study, the actual conditions of energy consumption are researched, and the relation between the facility area, the number of classes and students, and the cooling and heating facilities is analyzed. And then, the basic data required for energy-saving strategies at school facilities are prepared. In conclusion, the energy consumption of the surveyed schools is increasing. The total annual energy consumption of each school is estimated to be 400–1750[MWh/yr], which varies between schools depending on the scale. The electric power consumption accounted for approx. 82% of the total energy consumption of the surveyed schools, and LNG and kerosene accounted for 14% and 4%, respectively. The schools using fans for cooling had significantly lower energy consumption than the schools with Electric Heat Pump(EHP). The annual energy consumption per unit area of the surveyed schools is approx. 67–240[kWh/m2/yr], and the annual average energy consumption per unit area is 133[kWh/m2/yr]. However, there is no significant difference in energy consumption per student. These results can be caused by various reasons, but are especially related with the size of school and the number of classes. Keywords: Middle schools, Buildings, Energy, Educational facilities, Energy consumption